2010
DOI: 10.4049/jimmunol.1001397
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Key Variables for the Induction of Optimal NY-ESO-1–Specific T Cells in HLA Transgene Mice

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The therapeutic efficacy was associated with a Th1/Tc1 cytokine profile consisting of increased IFN-γ, TNF-α, and IL-2 cytokine production and a concomitant decrease in Th2 cytokines such as IL-4, IL-5, and IL-13. We also observed a significant increase in CCL3 (MIP-1α) and CCL4 (MIP-1β) chemokine expression, 19 which have been shown to enhance CD8 + T cell differentiation and dendritic cell function 32-35 . Additional studies are underway to elucidate the mechanisms by which CCL3 and/or CCL4 affect CD8 + T cell expansion and effector function following combination immunotherapy.…”
mentioning
confidence: 63%
“…The therapeutic efficacy was associated with a Th1/Tc1 cytokine profile consisting of increased IFN-γ, TNF-α, and IL-2 cytokine production and a concomitant decrease in Th2 cytokines such as IL-4, IL-5, and IL-13. We also observed a significant increase in CCL3 (MIP-1α) and CCL4 (MIP-1β) chemokine expression, 19 which have been shown to enhance CD8 + T cell differentiation and dendritic cell function 32-35 . Additional studies are underway to elucidate the mechanisms by which CCL3 and/or CCL4 affect CD8 + T cell expansion and effector function following combination immunotherapy.…”
mentioning
confidence: 63%
“…Johannsen and colleagues revealed that the T-helper (T H )1-associated cytokines IFN-g and IL-2 played key roles in CTL priming by upregulating the chemokine receptor on naive CD8 þ T cells (36). IFN-g induces T H 0 cells to differentiate toward T H l cells, promoting the T H l cell response and thus regulating the balance of T H l/T H 2 (37).…”
Section: Discussionmentioning
confidence: 99%
“…Different homologous and heterologous prime-boost vaccine strategies are currently being tested in the effort to develop effective vaccine responses against AIDS, as well as other infectious diseases and cancer and hold significant promise [117][118][119][120][121][122]. A sequential vaccination with DNA prime and recombinant viral vectors encoding multiple HIV genes boost has proven effective in eliciting robust CD8 + T cell responses in multiple animal models [38] as well as humans [121,123].…”
Section: Generation Of Functional Active Hiv-1-specific Immune Responmentioning
confidence: 99%